비가연성 5성분계 혼합냉매 조성변화에 따른 줄-톰슨 사이클 성능특성 - 최지후(Ji-Hoo Choi); 박성수(Sung-Soo Park); 이선근(Sun-Geun Lee); 윤지훈(Ji-Hoon Yoon); 손창효(Chang-Hyo Son); 윤정인(Jung-In Yoon) (동력시스템공학회지, 2020)
이 논문은 시뮬레이션 분석을 통해 Joule-Thomson 사이클의 비가연성 혼합냉매의 열역학적 측면을 분석하였다. 최근 에너지 효율이 주목됨에 따라 혼합냉매의 조성 최적화 역시 강조되고 있습니다. 그러나 비가연성 혼합냉매 사이클이 170-288K의 온도 범위에 최적화 된 경우는 거의 없습니다. HYSYS 시뮬레이션 프로그램을 사용하여 170-288K의 온도범위에서 5성분 R-245fa, R-134a, R-404A, R-23 및 R-14 혼합냉매의 조성비가 최적화 되었습니다. 이 분석을 통해 각 냉매의 냉매 특성을 추가 분석하였다. 특히 고압과 저압의 압력차에 따른 엔탈피 차와 중간 열교환기의 온도 변화를 통해 최적의 조성비를 선정하였다. Energy efficiency has been appeared in the spotlight recently. For this reason, the optimization of mixed refrigerant is also being highlighted. However, there are very few cases where non-flammable ones are optimized for the 170-288K temperature range. This paper analyzes from thermodynamic aspects of non-flammable mixed refrigerants in the Joule-Thomson cycle by simulation. In the temperature range of 170-288K, the composition ratio of the mixed refrigerants of five-component, R-245fa, R-134a, R-404A, R-23 and R-14 was optimized. Through this analysis, the refrigeration characteristics of each refrigerant were analyzed. In particular, the optimal composition ratio was found through temperature changes in enthalpy difference and intermediate heat exchanger with pressure difference between high and low pressure. KCI Citation Count: 3